1992
DOI: 10.1128/iai.60.7.2598-2604.1992
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Porphyromonas gingivalis adhesion to Streptococcus gordonii by human submandibular-sublingual saliva

Abstract: Porphyromonas gingivalis W50 adheres in vitro to biofilms of Streptococcus gordonii G9B. This phenomenon is believed to facilitate the initial colonization of the oral cavity by P. gingivalis and to contribute to the maturation of dental plaque. In this report, we describe the modulating effects of human submandibularsublingual saliva (HSMSL) on this in vitro model of intergeneric bacterial adhesion (coaggregation). HSMSL inhibited P. gingivalis adhesion to S. gordonii by 50% at a concentration of 57 t.g of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…Thus, it is conceivable that salivary tnolecules are bound to a significant portion of the cell surface altering or masking the adhesins. The small coaggregation effect observed in the current study supports the notion that saliva may mask specific coaggregations (21,30). However, the bacterial pellicle may not fonn spontaneously and salivary masking may not occur until sufficient time has elapsed.…”
Section: I'orph Vroiuonas Gingivalis Atcc 33277 Atcc 25260supporting
confidence: 77%
“…Thus, it is conceivable that salivary tnolecules are bound to a significant portion of the cell surface altering or masking the adhesins. The small coaggregation effect observed in the current study supports the notion that saliva may mask specific coaggregations (21,30). However, the bacterial pellicle may not fonn spontaneously and salivary masking may not occur until sufficient time has elapsed.…”
Section: I'orph Vroiuonas Gingivalis Atcc 33277 Atcc 25260supporting
confidence: 77%
“…Fibrinogenolysis by P. gingivalis W12 generated two main cleavage products (Mr 97 kDa and 50 kDa) (8), whereas P. gingivalis 381 could degrade fibrinogen to lower-molecularweight components. Stinson et al (19) showed that the adhesion of P. gingivalis W50 to S. gordonii G9B was inhibited by a 43 kDa protein purified from submandibular-sublingual saliva. The binding of the intact salivary component to P. gingivalis did not occur unless the bacterial surface proteases were inactivated by phenylmethylsulfonyl fluoride and sodium iodoacetate.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of fibrinogen to P. gingivalis 381 may be an important process in the inhibition of the coaggregation by fibrinogen. Several investigators suggested that the cell-associated proteases of P. gingi valis contribute to its coadhesion with gram-positive bacteria such as A. viscosus (11) and S. gordonii (19). Thus, the proteases of P. gingivalis that can bind fibrinogen might interact with the surface of S. oralis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27). Studies to date have demonstrated both an enhancement and inhibition of interbacterial adherence by saliva or salivary components, depending on the bacterial pair studied (13,21,23,26). Thus it is conceivable that the adsorption of saliva to different bacteria in the mouth will form different bacterial salivary pellicles, which could influence interbacterial adherence and thus subsequent plaque colonization.…”
mentioning
confidence: 99%